A web API service for calculating credit attributable to authors - Burgess, Marc (Department of Statistical Sciences, 2025)
The academic project “UniCoin” is designed to use the Ethereum blockchain to provide researchers with a way to licence their work. This provides a relatively economically efficient way to receive compensation for novel ideas, but is limited to research that is commercialisable. Foundational research is less commercialisable and is an environment where funding can be an issue. By considering the indirect impact of those providing the foundations upon which new research is built, it becomes possibly to more fairly allocate income and incentivise ongoing research. This research focusses on providing a means to allocate credit to the authors of works cited by research on the UniCoin platform by means of citation network analysis and the calculation of centrality measures. In particular, I present a web service that is able to generate citation networks for a given piece of research and from them to efficiently calculate measures of the contribution of other papers to the research. I demonstrate this functionality with case studies. This system can be integrated into UniCoin in order to provide a fair allocation of income to all contributors.